The Spiral Aftereffect Technique (SAT) Can Differentiate between Depressive and Somatoform Disorder Patients. Issue 2 (April 2014) - Olsson, Lars
This study examined how differences in visuo-perceptual patterns are related to psychopathology. Fifty-six patients (37 women, 19 men; M age = 43.8 yr., SD = 13.4) with a main diagnosis of unipolar depression and 42 patients (22 women, 20 men; M age = 42.0 yr., SD = 11.1) with a main diagnosis of somatoform disorder were compared. The duration and trend of a visual motion aftereffect were measured with the Spiral Aftereffect Technique (SAT). The results indicated that successively increasing aftereffect durations characterized the depressive patients, whereas patterns of very short or short final aftereffect preceded by successively decreasing aftereffect durations characterized the patients with a somatoform disorder. The SAT is thus a valuable tool for linking objectively measured perceptual-personality characteristics with some mental disorders.